2013
DOI: 10.3136/fstr.19.623
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant Activity and In Vivo Anti-fatigue Effects of Oyster (Ostrea plicatula Gmelin) Peptides Prepared Using Neutral Proteinase

Abstract: The amino acid profile of oyster (Ostrea plicatula Gmelin) peptides (OP) was assayed. Its in vitro antioxidant activity was determined, and its in vivo anti-fatigue activity was compared with those of oyster meat and oyster protein. Seven amino acids that may play an important role in enhancing antioxidant activity account for 25.8% of total OP content. These amino acids are histidine, proline, methionine, cysteine, tyrosine, tryptophan, and phenylalanine. The F-value of OP was 4.89, and the concentration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…It has been found that peptides containing glutamic acid or glutamic acid have high activity of scavenging free radical . Several amino acids, such as tyrosine, proline, methionine, lysine, histidine and tryptophan, can enhance the antioxidant activities of peptides . The total content of the seven amino acids mentioned above in SCP was 34%, indicating SCP might have latent antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that peptides containing glutamic acid or glutamic acid have high activity of scavenging free radical . Several amino acids, such as tyrosine, proline, methionine, lysine, histidine and tryptophan, can enhance the antioxidant activities of peptides . The total content of the seven amino acids mentioned above in SCP was 34%, indicating SCP might have latent antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…31 Several amino acids, such as tyrosine, proline, methionine, lysine, histidine and tryptophan, can enhance the antioxidant activities of peptides. 32,33 The total content of the seven amino acids mentioned above in SCP was 34%, indicating SCP might have latent antioxidant activity. Some amino acids are thought to be associated with the regulatory metabolism involved in muscular activity; they can improve exercise capability and remarkably slow down the catabolism of proteins in the muscle during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, OPs can increase muscle and liver glycogen levels, as well as supplement glycogen replenishment during strenuous exercise. 134 Moreover, OPs have been found to significantly reduce serum levels of lactic acid and blood urea nitrogen (BUN), both indicators used in in vitro evaluation of anti-fatigue drugs and human endurance. 13,135 Oyster peptides also possess demonstrated anticoagulant and antithrombotic properties.…”
Section: Other Bioactivitiesmentioning
confidence: 99%
“…An increase in LDH would accelerate the glycolysis process, producing more energy as well as blood lactic acid (BLA). Lactic acid may cause fatigue according to Hill and Kupalov's research (Hill, et al, 1929), so it is also often detected as an indicator in anti-fatigue tests (Hao, Cao, Hao and Zhang, 2013;Xu, Lv, Lo, Cui, Hu and Fan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in LDH would accelerate the glycolysis process, producing more energy as well as blood lactic acid (BLA). Lactic acid may cause fatigue according to Hill and Kupalov's research (Hill, et al, 1929), so it is also often detected as an indicator in anti-fatigue tests (Hao, Cao, Hao and Zhang, 2013;Xu, Lv, Lo, Cui, Hu and Fan, 2012).Glycogen, including liver glycogen (LG) and muscle glycogen (MG), is an important energy source stored in the body. Glycogen could be used to complement the consumption of blood sugar (Ren, Zhao, Wang, Cui and You, 2011;Shao, Wang and Zheng, 2013).…”
mentioning
confidence: 99%